Empowering Small and Medium Enterprises (SMEs) in facing ASEAN-China Free Trade Area (ACFTA) - Abdullah, Moha Asri; Hoetoro, Arif (IIUM Press, 2015)

(untitled)
The ASEAN-China Free Trade Area (ACFTA) provides certain challenges, implications and opportunities to their member-countries. Faced with globalization of ACFTA, the issues articulate a number of propositions for SMEs in the region. The purpose of this paper is to address issues related to the readiness of Small and Medium Enterprises (SMEs) in facing the globalization by taking a special case of the ASEAN-China Free Trade Area (ACFTA). The methodology evaluates the macroeconomic overview of ASEAN-China economies, it elucidates economic cooperation and free trade area (FTA) between ASEAN and China by building ASEAN-China Free Trade Area (ACFTA). The findings have an important role in supporting national economic development and SMEs that can be observed in a number of aspects. The implementation of ACFTA will restructure regional industries and provide new challenges and opportunities to countries grouped in ASEAN whereby the SMEs, the dominant form of enterprises in ASEAN members, are generally not well positioned to respond to these challenges. Effective cooperation among SMEs through clustering strategy, can lead to achieve collective efficiency for gaining access to global markets beyond the reach of individual SMEs.